Supplier integration: A Proposed Practical Approach through a Matrix Comparing ABC Classification and Vendor Rating (International Journal of Applied Research in Management and Economics, 2023)
In the supplier evaluation process, companies focus on comparing performances. The literature offers various analysis methods, although the matrices used are often subjective and difficult to implement in practice. This article aims to develop an easily implementable model, aimed at meeting the company's need to identify suitable suppliers for integration projects. Integration involves establishing close collaboration and cooperation between suppliers and customers with the goal of reduced inventory levels, shorter delivery times, and improved customer service. Thanks to the collaboration of a sample of companies, a new model is proposed. Our research is structured in three phases: identification of parameters for supplier evaluation; creation of the matrix; evaluation of the satisfaction level reported by the companies that have used the model. A comparison matrix between ABC classes and a multi-criteria supplier evaluation index allow the company to define a set of suppliers with a high probability of integration. This practical approach has been implemented in approximately 23 companies, and the level of satisfaction reported is high because it demonstrates greater rationality in supplier evaluation.